GC-MS Assay to Alkaloid Extract of T. foenum-graecum Seeds and Detection Effect of Extract as Antibacterialect Of Extract As Antibacterial - Sura Salim Nadhm,; AL-Waheeb, Alla N. (University of Thi-Qar Journal of Science, 2024)
The need for standardized modern analytical procedures becomes urgent due to the rise in drug-resistant for pathogens. These procedures use to isolate new bioactive compounds from medicinal plants. The medicinal plant-derived compounds could provide a new method to fight pathogenic bacteria. This study sheds light on the antimicrobial activity of plant-derived components, their possible mechanisms of action, and their chemical potential. Five different plant extract concentrations were used:12.5, 25, 50, 100, and 200 mg/ ml. The maximum inhibition zone for the alkaloid extracted from seeds of Trigonella foenum against   Klebsiella pneumonia was (21.0 ± 0.63) mm at 200 Mg ml1 dose. In comparison, the minimum inhibition zone for Pseudomonas aeruginosa was (6.16 ± 0.40) mm at 25 Mg ml1. According to the results of the gas chromatography-mass spectrometry (GC-MS) analysis, the chemical composition analysis of the Trigonella foenum extract had a high concentration of organic components with antimicrobial and antioxidant properties.